Demographic, socioeconomic and lifestyle factors associated with sugar-sweetened beverage intake: a population-based study - Amanda Silva Fontes; Ana Carolina Pallottini; Diva Aliete dos Santos Vieira; Mariane de Mello Fontanelli; Dirce Maria Marchioni; Chester Luiz Galvão Cesar; Maria Cecilia Goi Porto Alves; Moisés Goldbaum; Regina Mara Fisberg (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Introduction: The intake of sugar-sweetened beverages (SSB) varies according to the characteristics of the population. Objective: To investigate the SSB intake and demographic, socioeconomic and lifestyle factors associated with its consumption in adolescents, adults, and older adults in São Paulo. Methods: Data were drawn from the Health Survey of São Paulo, a cross-sectional population-based study including 1,662 individuals aged 12 years or more. SSB were classified into six groups: sugar-sweetened sodas, sweetened coffee and tea, sweetened milk and dairy products, sweetened fruit juice, sweetened fruit drink, and total SSB. The association of each group with demographic, socioeconomic and lifestyle variables was assessed using linear regression models. Results: The mean SSB intake was 668.4 mL in adolescents, 502.6 mL in adults, and 358.2 mL in elderly adults. Sodas and sweetened coffee and tea represented had the greatest contribution to energy intake. SSB consumption was lower among female sex and higher among overweight adolescents, among sufficiently active adults, and among lower household per capita income older adults. Consumption of SSB was high, particularly among adolescents. Public policies are required in order to decrease the consumption of these beverages. Conclusion: Age group, sex, household per capita income, and body mass index status were associated with SSB intake.